Design and development of a novel pH triggered nanoemulsified in-situ ophthalmic gel of fluconazole: Ex-vivo transcorneal permeation, corneal toxicity and irritation testing. (May 2013) - Pathak, Mukesh K.; Chhabra, Gulshan; Pathak, Kamla
<x xml:space="preserve">Abstract</x> The objective of the present research was to develop a novel pH triggered nanoemulsified in-situ gel (NE-ISG) for ophthalmic delivery of fluconazole (FLZ) to enhance the permeation and residence time of the formulation, by overcoming the limitations associated with protective ocular barriers. Pseudoternary phase diagrams were constructed using capmul MCM (oil phase), tween 80 (surfactant) and transcutol P (cosurfactant) to identify the NE region. Nanoemulsions (NE1-NE6) of FLZ were prepared by spontaneous emulsification method and evaluated for various pharmacotechnical characteristics. NE4 was selected as optimized NE and was dispersed in carbopol 934 solution to form nanoemulsified sols (NE-ISG1 to NE-ISG5) that were expected to convert in to in-situ gels at corneal pH (7.4). The optimized NE-ISG was selected on the basis of gelation ability with a residence time up to or more than 6 h. Ex-vivo transcorneal permeation study displayed significantly higher (p < 0.05) permeation of FLZ from NE-ISG5 (337.67 µg/cm2) and NE4 (419.30 µg/cm2) than the commercial eye drops (112.92 µg/cm2). Hen's egg test-Chorioallantoic membrane (HET-CAM) test with zero score indicated the non-irritant property of developed NE-ISG5. Corneal toxicity study revealed no visual signs of tissue damage. Hence it can be concluded that NE-ISG5 may offer a more intensive treatment of ocular fungal infections due to higher permeation, prolonged precorneal residence time and sustained drug release along with higher in-vitro efficacy, safety and greater patient compliance.